Architectural control of polystyrene physical properties using branched anionic polymerization initiated at ambient temperature. Issue 10 (10th April 2020) - Alhilfi, Tamara; Chambon, Pierre; Rannard, Steve P.
Abstract: Ambient temperature‐initiated anionic polymerization has generated branched polystyrenes of varying molecular weights and architectures by inclusion of a distyryl branching comonomer into a conventional sec ‐Butylithium‐initiated polymerization of styrene. Primary chain length control within the branched polymers, and restriction of the branching points to varying segments of the primary chains, led to variations of glass transition temperature with no direct correlation to the branched polymer molecular weight but a strong relationship to the length of individual chains comprising the branched macromolecules. Abstract : Ambient temperature‐initiated anionic polymerization of styrene has been used to generate polymers of varying molecular weights and architectures. The branched polystyrenes did not show a conventional T g versus molecular weight relationship and analyses have shown a strong correlation to the degree of polymerization of the component chains and position of branched points between chains.